Study on Role of CECT Abdomen in Intestinal Obstruction: A Clinical Approach - Dudhwala, Mohammad Farooque G. (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Background: Intestinal obstruction, which can be either dynamic or adynamic, is a common clinical event. To avoid missing strangulation, the old adage "Never let the sun set or dawn on a clogged bowel" was taught. With its multiplanar reformatted imaging, helical CT can properly define the level, degree, origin, and problems associated with obstruction. Aim: Aim of the study was to depict the spectrum of MDCT findings in cases of small and large bowel obstruction and correlation of CT scan with intraoperative findings and the cause of intestinal obstruction. Methods: Contrast enhanced MDCT examination of 50 patients were prospectively included in the study who had evidence of clinical as well as MDCT evidence of bowel obstruction and in whom surgical/clinical follow-up for final diagnosis was available. CT scan was done in all the patients with MDCT (Brightspeed GE 16 slice system). The axial sections were reconstructed in coronal and saggital planes to determine site and cause of bowel obstruction. Results: The commonest cause of intestinal obstruction in adults in this study series was adhesions/bands in 38% cases. Out of 47 operated patients for intestinal obstruction, CT findings matched with intraoperative findings in 43 patients (91%) whereas cause of intestinal obstruction matched with CT findings in 37 patients (74%). Conclusions: Management decisions in intestinal obstruction remain notoriously difficult, relying on a combination of clinical, laboratory, and imaging factors to help stratify patients into conservative or surgical treatment. CT in these patients can help surgeon to go for surgery early and prevent complications.